Complementary Platforms - Jo Reynaerts; Patrick Van Cayseele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
We introduce an analytical framework close to the canonical model of platfirm competition investigated by Rochet and Tirole (2006) to study pricing decisions in two-sided markets when two or more platfirms are needed simultaneously for the successful completion of a transaction. The model developed is a natural extension of the Cournot-Ellet theory of complementary monopoly featuring clear cut asymmetric single- and multihoming patterns across the market. The results indicate that the so-called anticommons problem generalizes to two-sided markets because individual platfirms do not take into account the negative pricing externality they exert on the other platfirms. As a result, mergers between such platfirms may be welfare enhancing, but involve redistribution of surplus from one side of the market to the other. Moreover, the limit of an atomistic allocation of property rights however is not monopoly pricing, indicating that there also exist differences with the received theory of complementarity.
Keywords: D43; D62; K11; L13; L4; L5; 330; Two-Sided Markets; Complements; The Anticommons Problem; Marktmechanismus; Marktstruktur; Unvollkommener Markt; Theorie